New data on Marocella (Mollusca, Helcionelloida) from the Cambrian (Series 2–Miaolingian) of the Iberian Peninsula. (2nd July 2020) - Collantes, Luis; Mayoral, Eduardo; Chirivella, Juan B.; Gozalo, Rodolfo
ABSTRACT: The present work is an overview of the current knowledge about the genus Marocella on the Iberian Peninsula, describing new specimens from the lower and middle Cambrian (Cambrian Series 2 and Miaolingian) of the southwestern Ossa-Morena Zone and Iberian Chains. Specimens from the lower Cambrian of the Ossa-Morena Zone are described as M. morenensis . Also, we found specimens in the Iberian Chains, which have been described earlier from the Cantabrian Mountains and dealt with as Marocella cf. morenensis . These specimens were found in strata of the latest Stage 4 of Cambrian or earliest Wuliuan. The youngest specimens from the upper Leonian to middle Caesaraugustian regional Stage (Wuliuan to early Drumian) of Iberian Chains are newly discovered material and classified as M . aff. morenensis . On the basis of new material of M. morenensis, M. mira and M. morenensis are regarded as different species herein, and the biostratigraphic and palaeobiogeographic distribution of Marocella is reviewed.